An Evaluation of Football Coaches and Players via Football Work-Based Learning [F-WBL] Sport Science Approach - Abdul Rahman, Md. Baharuddin; Mahazir Ismail, Irwan; Binti Halim, Harliana; Asniza Ishak, Nor (International Journal of Psychosocial Rehabilitation, 2019)
This study aims to measure and evaluate the technical and understanding of coaches via the Football Work-Based Learning (F-WBL) module [ISBN 978-967-0783-33-8] pilot test. The process involved three phases: Phase 1, the formation of the F-WBL concept and items; Phase 2, the practical’s based on techniques at stage 1 of the F-WBL module; and Phase 3, the actual study and validation of the effectiveness of understanding of coaches (14 coaches) and football players (17 players) by entering a test at the end of the process. The Competencies-Based Analysis focuses on 2 main domains, which include understanding (cognitive) of F-WBL techniques & effectiveness (competencies) of F-WBL techniques. The data’s shown that for the domain understanding of the process F-WBL for coaches at 100%, but for domain understanding of the process F-WBL for players at 53%. This data means that all coaches entering the course understand the concept, but almost all players are still not fixed to fully fill the maximum need of F-WBL trainers. Almost all players should enter the next course to ensure they will meet the maximum standard of trainers F-WBL needs. This is about the quality of football player production, so all players should practice more to ensure all technical knowledge at stage 1 they can achieve to meet the maximum quality standard of F-WBL competency needs. This F-WBL development based on understanding and competency assessment looks full to fill the needs of football coaches and football player development in Malaysia. Hopefully this F-WBL module will work as a new sport science instrument for football player development.